The Opportunities of Using Malay Apple (Syzygium malaccense (L). Merr. & Perry) Wood Stem Extract as Halal and Thayyib Antidiabetic Drugs - Fauziah, Nenden; Senania, Astri; Nuari, Dhoni Anshar; Setianingrum, Marginingsih (Indonesian Journal of Halal Research, 2019)
The use of existing antidiabetic drugs generally causes dangerous side effects, while the use of insulin has a problem with the halal status of the ingredients. Treatment with halal and thayyib medicinal ingredients is needed by Muslims, so it is necessary to find antidiabetic drugs that are halal and thayyib. The use of natural materials such as malay apple can be a solution for halal medicine. The study on antihyperglycemic activity of extracts of malay apple stem wood have been done. Invivo studies were carried out on animal experiments in male swiss webster mice using the glucose tolerance method. The experimental results showed a decrease in blood glucose levels after feeding with extract of malay apple stem wood at doses of 100 mg/Kgbw, 200 mg/Kgbw and 400 mg/Kgbw, which were significantly different compared to the control group (p <0.05), but effective doses shown at a dose of 100 mg/Kgbw. Measurement of moisture and ash content, levels of heavy metal and microbial contamination, showed that the simplicia of malay apple stem wood is safe. The results of this study indicate that malay apple wood extract is a material that is very likely to be used as antidiabetic drugs that are halal and thayyib.